2020
DOI: 10.3390/app10031022
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Flow-Induced Noise Study for Centrifugal Pumps

Abstract: Flow-induced noise is a significant concern for the design and operation of centrifugal pumps. The negative impacts of flow-induced noise on operating stability, human health and the environment have been shown in many cases. This paper presents a comprehensive review of the flow-induced noise study for centrifugal pumps to synthesize the current study status. First, the generation mechanism and propagation route of flow-induced noise are discussed. Then, three kinds of study methodologies, including the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 76 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Cavitation is a common problem of centrifugal pumps, which can cause an increase in pump vibration and noise, decrease in performance, and cause serious damage to pump parts [ 31 , 32 ]. There are many reasons for cavitation, but from the perspective of vibration response, whether it is caused by turbulence, internal reflux, or other reasons, it will show a shock vibration response [ 33 ]. The vibration feature of such a cavitation fault is a continuous wide-band signal.…”
Section: Centrifugal Pump Operation Failure and Its Featuresmentioning
confidence: 99%
“…Cavitation is a common problem of centrifugal pumps, which can cause an increase in pump vibration and noise, decrease in performance, and cause serious damage to pump parts [ 31 , 32 ]. There are many reasons for cavitation, but from the perspective of vibration response, whether it is caused by turbulence, internal reflux, or other reasons, it will show a shock vibration response [ 33 ]. The vibration feature of such a cavitation fault is a continuous wide-band signal.…”
Section: Centrifugal Pump Operation Failure and Its Featuresmentioning
confidence: 99%
“…As a typical rotating machinery, research on the vibration and noise of centrifugal pumps has been fruitful at home and abroad [5][6][7][8][9]. Cheng et al [10] improved the noise of a centrifugal pump by cutting the outlet side of the impeller, and found that there exists an optimal cutting width to weaken the rotorstator interaction between the impeller and the volute, which effectively reduces its internal and external sound field.…”
Section: Introductionmentioning
confidence: 99%
“…The centrifugal pumps are the main fluid transporting devices, which have played an indispensable role in many fields [1][2][3]. With the increasingly stringent environmental requirements, on the basis of high hydraulic performance of centrifugal pumps, the noise performance has received wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of flow-induced noise was associated with various complex phenomena in pumps, including rotor-stator interaction and cavitation, etc. [3].…”
Section: Introductionmentioning
confidence: 99%